Awareness of Libyan Students and Academic Staff Members of Nanotechnology - Nagib A. Elmarzugi & & , Eseldin I. Keleb, Aref T. Mohamed, Huda M. Benyones, Nesrein M. Bendala, Abdulfattah I. Mehemed, Ahmad M. Eid (Journal of Applied Pharmaceutical Science, 2014)
At the present time, nanotechnology is involved in every aspect of scientific life and its applications are being integrated into the economy, industry, trade and medicine. The world will require a skilled work force of more than two million nanotechnologists by 2015. The rapid advance in all fields of nanotechnology has led to integrate nanotechnology courses in high schools, institutes and university curricula all over the world. However, nanotechnology has not as, yet been integrated within the Libyan curricula at any level. Thus, this study focuses and explores the awareness of the academic staff and students in Tripoli (Alfateh) University about nanotechnology and nanoscience. Moreover their readiness to integrate the basics and applications into Libyan education curricula. The results show that education level and work place have an effect on the knowledge of the participants on nanotechnology, where about 65% of PhD degree holders knew about nanotechnology and were keen to learn and integrate this technology in the education system. Around 40 % of the participants’ information about Nanotechnology were gained from the internet while only 17% had obtained information from their own readings. The majority of the participants (60%) supported the idea of introducing nanotechnology studies to the curricula at pre-graduate stage. However, 29% believed that it should be integrated only in postgraduate studies, and only a few of the participants (11.3%) advised that a continuing education program would be the proper way to study nanotechnology. This study showed that relatively little awareness about nanotechnology is seen among Libyan staff members and students. However, the majority of the participants have realized the importance of the field of nanotechnology and its application, and were eager to learn more about this advanced technology. Based on the preliminary study regarding the opinion and readiness of participants of the current study, it is believed that the integration of nanotechnology and nanosciences in Libyan curricula at different levels of education is an inevitable step to meet the very rapid advances in the field of nanotechnology and its applications.
Keywords: Nanotechnology,awareness,nanoeducation,nanoscience,Libya.